Reply to Mr. Dotan: Using VO2max as a marker of training status in athletes - can we do better? - Podlogar, T.; Leo, P.; Spragg, J. (Journal of Applied Physiology, 2023)
Although we were surprised by the timing, we would nevertheless like to thank Mr. Dotan for his comment (1) on our Viewpoint. Mr. Dotan reiterates our main point that maximal oxygen uptake (Vo2max) is an insufficient metric when classifying participants and describing the training status.